A Philosophical Dictionary, Volume 10 - Voltaire, 1694-1778; Leigh, Oliver Herbrand Gordon; Morley, John, 1838-1923; Smollett, T. (Tobias), 1721-1771; Fleming, William F. (Salt Lake City, UT : Project Gutenberg, 2011)
"A Philosophical Dictionary, Volume 10" by Voltaire is an encyclopedic dictionary published in 1764. This alphabetically arranged work boldly critiques the Roman Catholic Church, Judaism, Islam, and other institutions of its era. Born from a dinner party game at Frederick II's court, the portable volume was designed to fit in one's pocket and make revolutionary ideas accessible to ordinary people. Shaped by Voltaire's experiences in England and events like the Calas affair, the dictionary champions deism, tolerance, and press freedom while challenging religious authority$1 (Bearning both public acclaim and official censorship across Europe. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dictionnaire_philosophique
Release date is 2011-03-29
Produced by Andrea Ball, Christine Bell & Marc D'Hooghe (From images generously made available by the Internet Archive.)
Keywords: Philosophy -- Dictionaries; Criticism (Philosophy)